Effect of the iron-containing filler on the strength of concrete - Shishkin, Alexsander; Netesa, Mikolay; Scherba, Vladimir (Eastern-European Journal of Enterprise Technologies, 2017)
The purpose of present research is to determine the impact of a mixture of river and technogenic sand containing iron compounds in the presence of plasticizers on the strength of fine-grained concretes. As a result of the performed research it was established that the technogenic sand, representing mineral complexes containing iron compounds, interacts with Portland cement minerals and the products of their hydration. The studies we conducted showed the possibility of targeted regulation of the processes of formation of structure of fine-grained concretes by joint application of mineral complex with iron ions, river sand and surface-active substances that are substantially different in the structure of molecules. It was established that using a mixture of river and technogenic sand containing iron compounds in the form of a fine aggregate leads to a significant increase in concrete strength. There is a certain ratio between river sand and the technogenic sand containing iron compounds, which provides concrete with the largest strength. An optimal content of the technogenic sand in a fine aggregate depends on the type and amount of minerals within its structure, and the content of particles with different size. It is demonstrated that the effectiveness of using modern superplasticizers in fine-grained concretes increases considerably with the introduction of mineral complexes containing ions of iron to the compositions of concrete.